2021
DOI: 10.1080/1331677x.2020.1865181
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility and firms’ financial performance: a multi-level serial analysis underpinning social identity theory

Abstract: This research aims to investigate how firms' Corporate Social Responsibility (CSR) perception and disclosure derive accounting, market, and perception-based Firms' Financial Performance (FFP) through the serial mediation of individual-level organizational identification (OID) and employees' innovative job performance (EIJP). Philosophically, this research comes under the beliefs or worldview of postpositivism and employed a quantitative research design. And thus, the approach to theory development is deductive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 68 publications
2
18
0
Order By: Relevance
“…Some authors consider CSR actions as "marketing techniques that enable companies to simultaneously pursue economic and social goals" [43]. The complexity of the CSR construct has very different objectives because it aims to satisfy other stakeholders and not all of them have the same interest in the firm's performance [18]. From a strategic point of view, CSR contributes to increasing a firm's value through superior competitive advantage [40], which may be related to human, organizational, or relational elements [5].…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
See 2 more Smart Citations
“…Some authors consider CSR actions as "marketing techniques that enable companies to simultaneously pursue economic and social goals" [43]. The complexity of the CSR construct has very different objectives because it aims to satisfy other stakeholders and not all of them have the same interest in the firm's performance [18]. From a strategic point of view, CSR contributes to increasing a firm's value through superior competitive advantage [40], which may be related to human, organizational, or relational elements [5].…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
“…In this sense, specific works suggest a direct link between CSR-employee behavior [20] and CSR-customer satisfaction [22]. When the firms adopt CSR practices, it contributes to building closer relationships with their stakeholders [43], and particularly in human resources management, customer satisfaction or firm reputation [18].…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have adopted social identity theory to explain how CSR creates a virtuous reputation and encourages employees to identify with their companies. Mahmood et al [44] showed that, when an organization engages in CSR activities, its members value being part of that organization, have a sense of belonging, and feel positive and respectful about the business. In the context of tourism and hospitality, Kim et al [45] used social identity theory to show that employees feel personal pride if their organization cares about CSR activities.…”
Section: Social Identity Theorymentioning
confidence: 99%
“…Hao and Li (2018) constructed an index system from three aspects, namely, managerial characteristics, enterprise characteristics, and social supervision characteristics, and established an ordered profit model to study the influencing factors of CSR fulfillment ( Hao and Li, 2018 ). Mahmood et al (2021) studied the influencing factors and economic consequences of CSR and found that CSR is conducive to the improvement of corporate performance ( Mahmood et al, 2021 ). Liu X. P. et al (2020) explored the influencing factors of consumer willingness to continue to participate in CSR activities, such as “CSR-CA,” “social existence,” and “self-construction,” with the help of relevant theoretical perspectives in social media and other fields ( Liu X. P. et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%